Hermeneutic of Dematerialization Discourse - Kosar Jalal Muhamad Kaka; Jaza Baker Mahmood (QALAAI ZANIST JOURNAL, 2024)
This research study focuses on (Analyzing the discourse of dematerialization in the Kurdistan Region, specifically in Sulaimanyah), and it consists of four chapters. The first chapter addresses the research issue, its significance, purpose, and limitations. This study aims to uncover the characteristics of dematerialized artworks created by Kurdish artists in the Kurdistan Region (especially Sulaimanyah) between 2008 and 2017. It also includes an exploration of the related keywords and their analysis in terms of linguistics, terminology, and definitions, according to the guidelines. The second chapter presents the theoretical framework, consisting of two topics. The first topic analyzes the concepts of hermeneutics and discourse, while the second topic delves into the concept of dematerialization (including its origins, references, and emergence), as an introduction and emergence of this concept in visual artwork. The third chapter outlines the methods and procedures used for analysis. The study employs a descriptive method of analysis, starting with the collection of artistic products and concluding with specific examples that are analyzed. The results obtained directly answer the research problem. The fourth chapter encompasses the study’s findings, conclusions, and recommendations. It includes insights drawn from each example and explores the characteristics of dematerialization in the context of visual art. Additionally, a list of references is provided